Agroforestry as an approach to rehabilitating degraded tropical peatland in Indonesia - Jaya, Adi; Dohong, Salampak; Page, Susan E.; Saptono, Mofit; Supriati, Lilies; Winerungan, Shella; Sutriadi, Mas Teddy; Widiastuti , Lusia (Brawijaya University, 2024)
Peatland is a unique ecosystem with water saturation; peatland regulates hydrological processes, climate, environmental conditions, and biodiversity. Poor management practises regarding peatlands can lead to land degradation, and peatland degradation typically has negative effects. Recent tropical peatland research in Indonesia has predominantly revolved around the examination of the ecological consequences resulting from various management approaches. There is little study on farmers' agroforestry efforts to preserve and restore degraded peatlands. A comprehensive examination was undertaken to assess a range of facts, information, and scholarly articles pertaining to the practise of agroforestry on peatlands in Indonesia. The primary incentive for farmers to adopt agroforestry systems originates from their recognition of the impending scarcity of trees. By integrating intercrops with cultivated trees, farmers anticipate generating adequate money to fulfil their family's economic requirements. Farmers who choose intensive intercropping practises are motivated by market demand, whereas farmers who do not adopt this approach tend to favour crops that necessitate less rigorous management. The provision of governmental assistance holds significant importance, and there is a pressing need for additional guidance and support. The potential for rehabilitating degraded peatlands by the implementation of agroforestry practises of native tree species is considerable. Their growth patterns contribute to enhanced vegetative coverage, resulting in heightened moisture levels, reduced temperatures, diminished fire hazards, and improved peat soil quality. The relationship between the physiography of the land and the depth of the peat is directly associated with the patterns and components of agroforestry in peatland environments.